Causal Influence between the JSX Composite Index and the FTSE Straits Times Index in Time Series - Muktar Redy Susila (Jurnal Ekonomi Pembangunan, 2022)
This research analyzes the causal influence between the JSX Composite Index and the FTSE Straits Times Index. The data used in this study is a monthly period time series data. The period for the JCI to be observed is January 2015 to June 2022. The VAR method was used to analyze the causal influence of the two indices. The analysis results show that the appropriate VAR model is VAR ( 1,4,5), RMSE value of 212.15 for the JSX Composite Index and 123.76 for the FTSE Straits Times Index. Based on the analysis results using the VAR model, information is obtained that the two indices influence each other. The value of the JSX Composite Index formed in the current period is controlled by the value of the JSX Composite Index and the FTSE Straits Times Index in the previous period. Likewise, for the FTSE Straits Times Index, the results show that the value of the FTSE Straits Times Index formed in the current period is influenced by the value of the JSX Composite Index and the FTSE Straits Times Index in the previous period.